Rapid Rates of Change in Multiple Biodiversity Measures in Breeding Avian Assemblages - Marlen Acosta Alamo; Lisa L. Manne (Diversity, 2025)
Species respond to environmental changes at different rates, resulting in no change, increased, or decreased resemblance among species assemblages. We explored the patterns of rate of change in bird diversity in five ecoregions of the United States across 30 years. We characterized the rate of change in breeding avian biodiversity using measures of species richness and assemblage dissimilarity, detecting changes in the same for 50% and 70% of the assemblages, respectively. Fast richness declines and species replacement were associated with rapid biotic differentiation within ecoregions, while rapid increases in richness and slowed species replacement were tied to high within-ecoregion biotic homogenization rates. Further, it was exceedingly rare for any biodiversity measured to change slowly over time; most changes were rapid. For the species assemblages studied here, changes in assemblage dissimilarity patterns were more common than changes in species richness, even though species richness has received more research attention. These results underscore the need to combine measures capturing different aspects of biodiversity (e.g., species richness and assemblage differentiation) to provide greater insight into the underlying mechanisms and pathways driving changes in biodiversity patterns.